MAIN PRINCIPLES OF LEARNER CENTERED APPROACH: MAIN PRINCIPLES OF LEARNER CENTERED APPROACH. - Kalmuratova, Nursuliw (Журнал иностранных языков и лингвистики, 2025)
As it was mentioned in the previous subchapter, the learner centered approach to language teaching and learning deals with the study of relationships between individual differences of learners and language acquisition development, therefore, this issue is of great importance in modern language teaching methodology. To be more precise, learners in one classroom can be different and individual in terms of language acquisition success due to the discussed factors before. In its own turn, this puts the problem of implementing the principles of learner centered approach into the focus of educational purpose of FLT. This makes it clear that learners should be approached to meet the needs of all learners in language classrooms. This process is achieved by using some principles or criteria of learner centered approach. Before outlining the linguodidactic potential of the principles of learner centered approach, firstly, it is essential to distinguish main principles of learner centered approach.